OBJN index 2004 - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2004)
ORIGINAL ARTICLESClowns doctors: the child talk. (text in Portuguese) Interfaces of geriatric nursing and dental care.(text in Portuguese)Mortality for Accidents of Traffic in Rio Branco – Acre - Brazil, 2001 to 2003.(text in Portuguese)Nursing diagnosis of patients with myocardial infarction, according to the conceptual model of Florence Nightingale. (text in Portuguese)Nursing process: application to the professional practice. (text in Portuguese)Participation of nursing students in the network for the prevention of occupational accidents - REPAT. (text in Portuguese)The american tegumentary leishmaniasis in the perspective of who lives it. (text in Portuguese)The nurse’s leadership: challenges of the practice. (text in Portuguese)Understanding functional health literacy in experiences with prostate cancer: older men as consumers of health information. (text in English)Vancomycin administration in an universitary hospital at general surgical units inpatients (text in Portuguese)We have needs, too: parental needs during a child’s hospitalisation.(text in English)Work accidents with needles and other sharp medical devices in the nursing team at public hospitals - Rio Branco, Acre - Brazil.(text in Portuguese)REVIEW ARTICL ESGender, health and nursing: The male inclusion in the nursing care. (text in Portuguese)Influence of psychosociais needs in the mental health of the children.(text in Portuguese)Literature review on ineffective thermoregulation – OBNJ Club Journal.(text in Portuguese)Literature review on Neonatal Pain – OBJN Club Journal. (text in Portuguese)Literature review on newbons care –  OBJN Club Journal.(text in Portuguese)Literature review on risk for impaired parenting – OBJN Club Journal.  (text in Portuguese)Literature review on risk of infection in intravenous catheter related to the dialysis treatment – OBJN Club Journal. (text in Portuguese)Public policies regarding family, institutional requirement from the politics philosophy of Hegel and Marx.(text in Portuguese)Review of research about parish nursing practice (text in English)The civil responsibility of nurse  as a public agent. (text in Portuguese)The contribution of philosophy, ethics, and bioethics in the Ribeirão Preto School of Nursing – USP(text in Portuguese)The importance of the insert of the thematic " violence against the woman " in the curriculum of nursing. (text in Portuguese)Work of nursing in the family health program of and its relation with the non-institucionalization.(text in Portuguese)ABSTRACTSConstruction and validation of an instrument of collection of data of the aged one in the Program of Health of the Family.Construction and validation of data collection instrument for children from 0 - 5 years.Interaction among teachers and students in the construction of the nurses professional identityKnowledge and practice of beginner and veteran (men and women) nurses in the hospital scenarioNursing in field from training: “ Natural Lab” a professional learningPsycossocial Necessities of the Client at the Unit of Chest Pain: issues for caring in the Emergency Room.The social representation  of family:  expectation and meaning of cardiac surgery.(text in English)PROFESSIONAL ISSUES2004 Brazilian Women Year:Visual reflections related to the female sexuality in a feminine (sexy) Brazil focusing the female nurse.(pps in Portuguese)  5th European Conference of ACENDIO: Association for Common European Nursing Diagnoses, Interventions and Outcomes (text in English)NURSES: Working with the Poor; Against Poverty. Message from ICN (text in English)OBJN 2004 thanks to the Editorial and Peer-Review Board  (text in English)The Professional Master in Nursing Website (EEAAC/UFF): linking knowledge to nursing practice (text in Portuguese)Thirteen National Brazilian Nursing Research Congress (SENPE) June 2005, São Luiz, Maranhão.World Health Organization: Forum 8 + World Summit on Health ResearchMexico City, November 6-10, 2004 (text in English)